REGULASI PERDAGANGAN TERKAIT PERLINDUNGAN PRIVASI KONSUMEN DALAM EKSPANSI BISNIS DI UNI EROPA: STUDI KASUS ALIBABA - Leonora, Gracella; Pratikno, Roy Vincentius (Universitas Pelita Harapan, 2024)
The European Union (EU) has implemented stringent trade regulations, particularly regarding consumer privacy protection governed by the General Data Protection Regulation (GDPR). Countries or organizations facing privacy issues or lacking adequate data protection standards must encounter barriers in business expansion in the EU. Through a case study of Alibaba, this research specifically analyzes the challenges and GDPR compliance strategies in business expansion within the European Union. The study investigates the implementation of GDPR in the EU and analyzes all the strategies and actions taken by Alibaba to comply with GDPR. The research framework is based on Neoliberalism theory, as well as international trade concepts, privacy and personal data concepts, public authority concepts, and multinational corporation concepts. The research employs a qualitative approach with descriptive research methods and a case study. Data were obtained from secondary sources and analyzed using narrative analysis techniques. The study analyzes the economic relationship between the EU and China as a background, reviews the development of consumer privacy protection regulations in the EU, and analyzes Alibaba's expansion strategy in the EU. Based on the research findings, GDPR does not allow countries/companies with privacy issues and inadequate data protection to operate in the EU. As a company meeting these violation criteria, Alibaba successfully expanded in the EU by addressing internal issues and establishing regulations compliant with GDPR in each of its subsidiaries.